Solar Distillation in India - Gomkale, S D; Datta, R L (Annals of Arid Zone, 2016)
The paper reviews the work carried out in India on solar distillation in conventional simple glass covered solar stills. Extensive experimental work has been carried out in this field at the Central Salt & Marine Chemicals Research Institute, Bhavnagar and a number of solar distillation plants ranging from laboratory size (a few litres per day) to medium size (a few hundred litres per day) have already been installed at various places. Solar distillation may be a suitable solution for getting potable water for isolated communities having saline water resources and abundant solar energy.